2020
DOI: 10.1093/cid/ciaa1475
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronavirus Disease 2019 Public Health Measures on Detections of Influenza and Respiratory Syncytial Virus in Children During the 2020 Australian Winter

Abstract: Public health measures during the COVID-19 pandemic have potential to impact transmission of other respiratory viruses. We found 98.0% and 99.4% reductions in RSV and influenza detections respectively in Western Australian children through winter 2020; despite reopening of schools. Border closures have likely been important in limiting introductions from abroad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
390
3
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(453 citation statements)
references
References 7 publications
51
390
3
9
Order By: Relevance
“…As of July 2020, NYC appears to be slowly recovering, with many New Yorkers returning to work and the resumption of non-essential services; yet, the PED visit volume remains low compared to the year prior. The emphasis placed on self-protection with face coverings, frequent hand washing and social distancing are likely to extend beyond the pandemic and may reduce subsequent viral exposure [ 39 ], having a lasting effect on the wellbeing of children.…”
Section: Discussionmentioning
confidence: 99%
“…As of July 2020, NYC appears to be slowly recovering, with many New Yorkers returning to work and the resumption of non-essential services; yet, the PED visit volume remains low compared to the year prior. The emphasis placed on self-protection with face coverings, frequent hand washing and social distancing are likely to extend beyond the pandemic and may reduce subsequent viral exposure [ 39 ], having a lasting effect on the wellbeing of children.…”
Section: Discussionmentioning
confidence: 99%
“…There is no vaccine for RSV, and the virus causes about 5% of deaths in children under five around the world. In Western Australia, RSV in children declined by 98% (and flu by 99.4%) through their winter 2020, even though schools were open 2 .…”
Section: Bucking the Trendmentioning
confidence: 99%
“…Several reports have shown that the incidence of specific pathogen infections such as influenza viruses, respiratory syncytial virus, meningococcus, and pneumococcus was reduced in many countries. 18 , 19 , 20 , 21 Australia reported a concurrent lower frequency of respiratory syncytial virus detection and admission to hospital for bronchiolitis in 2020 as compared with preceding years. 19 In this country, despite schools reopening, a 99.4% reduction was reported in influenza detection following Australian public health measures.…”
Section: Shift Of Paradigmmentioning
confidence: 96%
“… 19 In this country, despite schools reopening, a 99.4% reduction was reported in influenza detection following Australian public health measures. 21 Influenza data reported to the World Health Organization's FluNet platform from 3 Southern Hemisphere areas (Oceania, South America, and Southern Africa) showed very low influenza activity during June to August 2020. 18 These data suggest that the epidemiology of these infectious diseases may change in an unpredictable manner in the coming months and years, requiring close and active surveillance.…”
Section: Shift Of Paradigmmentioning
confidence: 99%
See 1 more Smart Citation